Investing in land and water management practices in the Ethiopian highlands - Gebresilase, Y.; Amede, Tilahun (Springer, 2014)
The Ethiopian highlands are characterized by land degradation, erosion and low productivity, while they serve as the water towers of the region. It is estimated that over 1.9 billion tons of soil are lost from the highlands of Ethiopia each year, with the soil loss ranging from 5 to 300 t/ha/year, depending on the land use. This is, on average, equivalent to a 2.5 cm depth of soil per hectare. Land degradation has been costing the country at least 2–3 % of the agricultural GDP. The direct cost of land degradation is not only nutrient loss but also reduction in crop and livestock productivity, increased incidence of forest removal and decreased farmland for the ever-increasing population. Moreover, the upstream land degradation is also costing downstream countries (Sudan and Egypt) from about US$280 to 480 million to clear sediments annually. There are tremendous efforts by the Ethiopian Government and its partners to minimize the negative effects of land degradation and improve the productivity of these lands. Case studies on the potential benefits of soil and water management indicate that organic matter content and crop yields increased up to three times, while nitrogen content has doubled in a 10-year time span. The benefits were much higher when the physical interventions were applied with vegetative measures (e.g., tree lucerne, vetiver, Napier grass). Interventions have also increased the water budget of the landscape, improved crop water productivity, and reduced nutrient movement. However, the adoption by farmers of Sustainable Land Management interventions was possible only when incentive mechanisms, including participatory planning processes, are used, collective action of communities and local authorities is created, short-term benefits addressing food and feed security are introduced, and a process of linking natural resource management with market opportunities is implemented. This paper highlights best-bets and innovations learned in land and water management research and development in Ethiopia over the last four decades, primarily from the experiences of the Soil Conservation Research Project (SCRP), the African Highlands Initiative program (AHI) and the ongoing, government-owned Sustainable Land Management program (SLM).